CFD analysis of existing Mobile Disinfecting Units (MDUs) - Constantino Ian Jimbo; Serrano Nicanor (E3S Web of Conferences, 2024)
The global economy, well-being, and public health are all gravely compromised by COVID-19. Thus, MDUs have been created to reduce such dilemmas. This document contains a study of a mobile disinfectant unit (MDU) that will mitigate the virus’ spread. By using simulation tools, a final design will be an overall improvement derived from the three models exhibited to generate simulations. Certain significant parameters were noted in doing the simulation, namely: (1) Contamination Removal Effectivity (CRE); (2) Air Distribution Performance Index (ADPI); and (3) Local Air Quality Index (LAQI). These are the coefficients that measure the units' effectiveness in lessening the contaminant present in ambient air and maintaining air comfortability. With the following parameters considered, an optimized design has been conceived having promising CRE, LAQI, and ADPI values by employing fluid machines such as fans, exhausters, and misting systems. Solidworks' CFD simulation concluded a better CRE and LAQI on the designed model than the existing ones having values close to 1, while its output ADPI is around 34%. Moreover, from the AnSys CFD simulation, the coverage area of the misting was around 95%, compared to its predecessors. These numbers prove that the designed model is indeed an enhancement of its predecessors.